Prevalence of Diabetic Retinopathy among Diagnosed Diabetics at Layton Rehmatullah Benevolent Trust (LRBT) Tertiary Eye Hospital, Korangi Karachi - uzma Ali Abbasi, Ali Hussain Khan, All Muhammad Abbasi, Khan Muhammad Nangrejo, amjad ali, Abdul Manan , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objectives: To determine the prevalence of Diabetic retinopathy among diagnosed Diabetes Mellitus patients at Diabetic Retinopathy clinic. Methods: A Hospital based cross- sectional study conducted on prevalence of diabetic retinopathy at Layton Rehmatullah Benevolent Trust Free Based (LRBT) Tertiary Eye Hospital, Korangi, Karachi from15th February to 31' April 2017. The totals of 390 study subjects were randomly enrolled in the study. The study included diabetic patients visiting LRBT, between the age 25-70 years, with clear ocular media, and HbA 1C level > 6.5% . Results: Study results revealed that out of 390 diabetic patients 40.3 % (157 were suffering from diabetic retinopathy). 59.2% (230) were males and 40.8% (160) females. Most of them were found between the ages of 41-50 years (17.9°A cases). Socio demographic factors like age were closely associated with diabetic retinopathy. Out of total 157 cases of diabetic retinopathy, the prevalence of non-proliferative Diabetic Retinopathy (NPDR) was present in 16.9 6/0 (66 patients) and 21.8%, had Proliferative Diabetic Retinopathy. Conclusion: The progression of diabetic retinopathy is related with duration of diabetes mellitus. Therefore, frequent follow-ups of diabetic patients by ophthalmologist are necessary to decrease the risk of diabetes occular complication and to improve the patient's quality of life.